1995
DOI: 10.1055/s-2006-958146
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-3-ols and Flavonoids fromPotentilla anserina

Abstract: Roots/rhizomes and aerial parts of Potentilla anserina L. (Rosaceae) contain two flavan-3-ols: (+)-catechin and (+)-gallocatechin. The flavonol glycosides and glucuronides isolated from the herb were kaempferol 3- O-beta- D-glucoside, kaempferol 3- O-beta- D-(6''- O-( E)- P-coumaroyl)glucopyranoside, quercetin 3- O-beta- D-glucoside, quercetin 3- O-beta- D-xyloside, quercetin 3- O-alpha- L-rhamnoside, quercetin 3- O-beta- D-sambubioside, quercetin 3- O-beta- D-glucuronide, isorhamnetin 3- O-beta- D-glucuronide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Potentilla anserina Kombal and Glasl (1995) Bate-Smith (1961) Krzaczek ( logical and histopathological studies confirmed the effectiveness of an orally administered extract of the leaves of this species for ethanol-induced peptic ulcers in rats (Gürbüz et al, 2005). Russian authors (Popov et al, 2006) obtained interesting results when testing the influence of comaruman, a pectin isolated from aerial parts of Comarum palustre (syn.…”
Section: Myricetin-3-o-␣-l-rhamnosidementioning
confidence: 92%
See 3 more Smart Citations
“…Potentilla anserina Kombal and Glasl (1995) Bate-Smith (1961) Krzaczek ( logical and histopathological studies confirmed the effectiveness of an orally administered extract of the leaves of this species for ethanol-induced peptic ulcers in rats (Gürbüz et al, 2005). Russian authors (Popov et al, 2006) obtained interesting results when testing the influence of comaruman, a pectin isolated from aerial parts of Comarum palustre (syn.…”
Section: Myricetin-3-o-␣-l-rhamnosidementioning
confidence: 92%
“…Potentilla anserina Kombal and Glasl (1995) Quercetin-3-O-␣-l-rhamnoside (quercitrin) Potentilla anserina; Potentilla fruticosa; Potentilla fragarioides Fedoseeva (1979) Kombal and Glasl (1995) Choi et al (1998) Quercetin-3-O-␣-l-arabinofuranoside Potentilla areata; Potentilla fruticosa d ; Potentilla discolor Klyshev and Pershukova (1989) Miliauskas et al (2004) Xue et al (2006) Quercetin-3-O-␣-l-arabinopyranoside Potentilla fruticosa Ganenko et al (1988) Quercetin-3 -glucoside Potentilla erecta; Potentilla reptans Harborne and Nash (1984) …”
Section: Quercetin-3-o-␤-d-xylosidementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the BtFlav3 fraction, its principally content was the flavonol 3-O-quercetin rhamnopyranoside (4), following by 3-O-quercetin glucopyranoside (5), and rutin (6). In the case of compounds 4 and 5, the identification was achieved by comparison between the experimental data obtained by spectroscopic and spectrometric data of the isolated compounds and the literature (Kombal and Glasl 1995;Yen et al 2009). The identification of compound 6 was determined by HPLC analysis when experimental peak overlapped with the commercial standard, although the detection wavelength was scanned at 190-400 nm.…”
Section: Phytochemical Analysis Of Bthamentioning
confidence: 99%